2020
DOI: 10.2147/ott.s235664
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of circRNA-miRNA-mRNA Networks for Exploring the Fundamental Mechanism in Lung Adenocarcinoma</p>

Abstract: Background: Circular RNAs (circRNAs) were elucidated to act as competing endogenous RNAs (ceRNAs) and to play significant roles in cancer initiation and progression. We aimed to identify the important circRNAs in lung adenocarcinoma and intended to predict the functions of them via the bioinformatics analysis. Methods: We extracted data from three Gene Expression Omnibus (GEO) datasets, GSE101586, GSE101684, and GSE104854, and identified the common differentially expressed circRNAs. Agarose gel electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Ten DEcircRNAs (5 upregulated and 5 downregulated) were signi cantly overlapped in two datasets, indicating important roles of circRNAs in LUAD. Moreover, hsa_circ_0000519 (circRNA-002178), hsa_circ_0072088 were identi ed, which were signi cantly upregulated in LUAD, and JunFeng Wang et al revealed that circRNA-002178 could act as a miRNA sponge to promote PDL1/PD1 expression in LUAD [35], Liming Liang et al con rmed that hsa_circ_0072088 were found differentially upregulated expression in LUAD with matched normal tissues by qRT-PCR with a P value < 0.05 [36]. However, circRNA-002178 was not in our ceRNA network based on our criteria (see methods).…”
Section: Discussionmentioning
confidence: 99%
“…Ten DEcircRNAs (5 upregulated and 5 downregulated) were signi cantly overlapped in two datasets, indicating important roles of circRNAs in LUAD. Moreover, hsa_circ_0000519 (circRNA-002178), hsa_circ_0072088 were identi ed, which were signi cantly upregulated in LUAD, and JunFeng Wang et al revealed that circRNA-002178 could act as a miRNA sponge to promote PDL1/PD1 expression in LUAD [35], Liming Liang et al con rmed that hsa_circ_0072088 were found differentially upregulated expression in LUAD with matched normal tissues by qRT-PCR with a P value < 0.05 [36]. However, circRNA-002178 was not in our ceRNA network based on our criteria (see methods).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Li et al (2020) used the same public datasets as this study, they took the union of GSE101586, GSE101684, and GSE11214 to identify differentially expressed circRNAs among NSCLC and healthy individuals for early diagnosis of NSCLC. Liang et al (2020) used the intersection of GSE101586, GSE101684 microarrays and GSE104854 high-throughput sequencing data to exploring the aberrant circRNAs and their potential molecular function in LUAD. Although the two GEO microarrays were same as ours, since high-throughput sequencing data and microarray data are different types, the results obtained by overlapping were different.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have reported the construction of circRNA-miRNA-mRNA regulatory networks in LUAD [17,18], the current understanding of circRNA-related ceRNA networks in LUAD is limited, and further study is needed. In this study, we identi ed a potential circRNA-miRNA-mRNA ceRNA regulatory network in LUAD.…”
Section: Discussionmentioning
confidence: 99%